2017
DOI: 10.7196/ajhpe.2017.v9i4.631
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Angoff method of standard setting using postgraduate students: Practical and affordable in resource-limited settings

Abstract: Background Cut scores for students’ assessments have always been arbitrarily determined in many institutions. Some institutions have adopted reliable methods of determining cut scores, such as the Angoff method. However, use of this method requires many experts, making it difficult to implement in resource-limited settings. The possibility of involving postgraduate students in implementing the Angoff method of setting cut scores could be the solution to this problem. Objectives To explore the knowledge and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…An adaptation of the modified Angoff method was used to categorize knowledge into satisfactory with score of 15 and above, and unsatisfactory with score below 15. [27][28][29][30] Independent variables were age, sex, education level, primary profession, having any form of medical education, any training attendance in the last one year, any supervision from government officials in the last one year, awareness of diarrhoea treatment recommendations, possession of iCCM guidelines, current availability of ORS, current availability of zinc, care-giver demand for ORS. Education level was dichotomized into primary, secondary and postsecondary levels.…”
Section: Variablesmentioning
confidence: 99%
“…An adaptation of the modified Angoff method was used to categorize knowledge into satisfactory with score of 15 and above, and unsatisfactory with score below 15. [27][28][29][30] Independent variables were age, sex, education level, primary profession, having any form of medical education, any training attendance in the last one year, any supervision from government officials in the last one year, awareness of diarrhoea treatment recommendations, possession of iCCM guidelines, current availability of ORS, current availability of zinc, care-giver demand for ORS. Education level was dichotomized into primary, secondary and postsecondary levels.…”
Section: Variablesmentioning
confidence: 99%
“…However, Senthong and others 18 showed that individual judges may also provide suitable cut-scores. Mubuuke and others 20 found that judges were biased in allocating scores where answers for the questions were provided and judges able to discuss cut-scores, and advised that the answers be withheld in order to avoid bias. Thus, the judges were requested to give their own opinions and were not given the answers to the questions in the assessment so that they could give an unbiased cutscore for each question.…”
Section: Methodsmentioning
confidence: 99%
“…1 The practical challenge of this method of convening judges has resulted in modiications of this method such as the modiied Angof method 17 and individual Angof method. 18 Generally, convening a large group of judges who are also familiar with test-takers 19 in order to set cutscores is often diicult, costly and impractical 20 and this would apply particularly to the veterinary profession where most of the judges would potentially be recruited from private practices. Even 15 judges as researched by Shulruf and others 16 is considered a large group in terms of practicality in the veterinary ield.…”
Section: Introductionmentioning
confidence: 99%
“…To decide a module's cut-off score, researchers have mostly used two popular methods, the Angoff method and the Cohen method (Jalil & Mortazhejri, 2012;Yim, 2018). According to Mubuuke et al (2017) and Assessment Strategies (2014), the Angoff method uses a group of experts to judge how difficult each item is in an exam to determine the cut-off score. The cut-off score (or mark) is like a line in the sand that divides students into two groups; those below the cut-off and those above the cut-off.…”
Section: Description Of the Digital Literacy Interventionmentioning
confidence: 99%